An Updated Review on Some Neurotoxicpharmacological Agents Along with their Neurotoxic Mechanisms (Medico Legal Update, 2021)
This review will provide the vital information about some pharmacological agents which are Neurotoxic.Through this update, Anti-cancer, Anti-bacterial, Analgesic, Psychoactive drug and Anabolic steroidmedication are reported briefly regarding their neurotoxic mechanisms. In this review all informationregarding neurotoxic drugsis collected from 2020 published work by Web of science, Scopus, PubMed andGoogle Scholar. It is concluded that all these drugs which the part of our study areneurotoxic. There is needto discover some methodto reduce their toxicity and to avoid the chronic use of these medications.